The American family in black and white: A post-racial strategy for improving skills to promote equality - James J. Heckman (Institute for the Study of Labor (IZA), 2011)
In contemporary America, racial gaps in achievement are primarily due to gaps in skills. Skill gaps emerge early before children enter school. Families are major producers of those skills. Inequality in performance in school is strongly linked to inequality in family environments. Schools do little to reduce or enlarge the gaps in skills that are present when children enter school. Parenting matters, and the true measure of child advantage and disadvantage is the quality of parenting received. A growing fraction of American children across all race and ethnic groups is being raised in dysfunctional families. Investment in the early lives of children in disadvantaged families will help close achievement gaps. America currently relies too much on schools and adolescent remediation strategies to solve problems that start in the preschool years. Policy should prevent rather than remediate. Voluntary, culturally sensitive support for parenting is a politically and economically palatable strategy that addresses problems common to all racial and ethnic groups.
urn:nbn:de:101:1-201104113680
Keywords: J15; J24; 330; skill gap; racial inequality; early childhood intervention; Kinder; Familie; Soziale Lage; Intelligenz; Schule; Bildungsertrag; Ethnische Gruppe; Sozialpolitik; Bildungschancen; USA